New host records and notes on Bruchidae (Coleoptera) from Leucaena Benth (Leguminosae, Mimosoideae) from Mexico, Central and South America - Hughes, C; Johnson, C (1996)
Twenty-five new Leucaena host records for five species of Acanthoscelides are reported and discussed in relation to previous reports on bruchid-host interactions for Leucaena. The ubiquitous occurrence of five Acanthoscelides species feeding on seeds of a wide range of Leucaena species is revealed and discussed in relation to the indigenous domestication of Leucaena in Mexico.